Investigating white matter changes in auditory cortex and association fibres related to speech processing in noise-induced hearing loss: a diffusion tensor imaging study - Zolkefley, Mohd Khairul Izamil; Abdull, Norhidayah; Shamsuddin Perisamy, Rajeev; Mustapha, Muzaimi; Adam, Daud; Muhamad Noordin, Muhamad Ariff (Springer Nature, 2024)
Background This study explores the impact of noise-induced hearing loss (NIHL) on the microstructural integrity of white matter tracts in the brain, focusing on areas involved in speech processing. While the primary impact of hearing loss occurs in the inner ear, these changes can extend to the central auditory pathways and have broader effects on brain function. Our research aimed to uncover the neural mechanisms underlying hearing loss-related deficits in speech perception and cognition among NIHL patients.